Comparing the American and European Perspectives on the International Concept of Andragogy and the Implications for the Development of Adult Education Theory and Practice - John A. Henschke; Mary K. Cooper (Adult Education Research Conference, 2008)
In this research paper we present a thorough picture of both the American and European perspectives on andragogy. We believe this to be much needed in the ongoing development of what many erroneously consider a static concept.
Keywords: andragogy; international; theorizing